2015
DOI: 10.1017/s1751731114002195
|View full text |Cite
|
Sign up to set email alerts
|

Selective mobilization of fatty acids in adipose tissue of heavy pigs

Abstract: The mobilization of fatty acids during food deprivation is a selective process studied in different species (humans, rodents, birds, viverrids). The aim of this work was to study the effect of fasting on selective mobilization in commercial pigs. A total of 16 barrows (Large White × Landrace (167 kg ± 12.5 kg live weight) were subdivided into two homogeneous groups, one subjected to 12 h and the other to 60 h of fasting (fasting time) before slaughtering. For each pig inner and outer backfat layer were sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A description of the preferred use of PUFA has been given, mainly n-3 from the tissues [29]. Also, Bochicchio et al [45] found a greater MUFA content but no effects on PUFA in the fatty acid profile of subcutaneous fat in 60 h-fasted pigs. This result could be explained, as in the present study, by a faster utilization of PUFA.…”
Section: Discussionmentioning
confidence: 99%
“…A description of the preferred use of PUFA has been given, mainly n-3 from the tissues [29]. Also, Bochicchio et al [45] found a greater MUFA content but no effects on PUFA in the fatty acid profile of subcutaneous fat in 60 h-fasted pigs. This result could be explained, as in the present study, by a faster utilization of PUFA.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that NEFA concentrations increase in chickens that were fasted ( Langslow et al, 1970 ; Van der Wal et al, 1999 ). Previous studies have shown that blood NEFA concentration and its oxidation increased with fasting time, resulting in increased malondialdehyde ( MDA ) concentrations in plasma and muscle in pigs ( Bochicchio et al, 2015 ; Rey et al, 2020 ). Although plasma NEFA concentration in fasting groups was high, there was no significant difference in MDA concentration in the postmortem pectoralis major muscle in the present study ( Supplementary Table S1 ).…”
Section: Discussionmentioning
confidence: 99%